Increasing plasma L-kynurenine impairs mitochondrial oxidative phosphorylation prior to the development of atrophy in murine skeletal muscle: A pilot study - Palzkill, Victoria R.; Thome, Trace; Murillo, Ania L.; Khattri, Ram B.; Ryan, Terence E. (Frontiers in Physiology, 2022)
Introduction: L-Kynurenine (L-Kyn), a product of tryptophan (Trp) catabolism, has been linked with impairments in walking speed, muscle strength/size, and physical function. The purpose of this pilot study was to develop a dietary model that elevates plasma L-Kyn levels in mice and characterize its impact on muscle health and function. Methods: Four-month-old C57BL6J male mice were randomized to either a L-Kyn supplemented (150mg/kg) or chow diet for ten weeks. Plasma L-Kyn and Trp levels were measured via mass spectrometry. Primary outcomes included assessments of muscle weights, myofiber cross-sectional area (CSA), nerve-stimulated contractile performance, and mitochondrial oxidative phosphorylation (OXPHOS) and hydrogen peroxide (H2O2) production. Additional experiments in cultured myotubes explored the impact of enhancing L-Kyn metabolism. Results: Mice randomized to the L-Kyn diet displayed significant increases in plasma L-Kyn levels (P=0.0028) and the L-Kyn/Trp ratio (P=0.011) when compared to chow fed mice. Food intake and body weights were not different between groups. There were no detectable differences in muscle weights, myofiber CSA, or contractile performance. L-Kyn fed mice displayed reductions in mitochondrial OXPHOS (P=0.05) and maximal ADP-stimulated respiration (P=0.0498). In cultured myotubes, overexpression of peroxisome proliferator-activated receptor-gamma coactivator 1 alpha prevented atrophy and proteolysis, as well as deficits in mitochondrial respiration with L-Kyn treatment. Conclusions: Dietary feeding of L-Kyn increases plasma L-Kyn levels and the L-Kyn/Trp ratio in healthy male mice. Mitochondrial impairments in muscle were observed in mice with elevated L-Kyn without changes in muscle size or function. Enhancing L-Kyn metabolism can protect against these effects in culture myotubes.